EXCESS OF MANDATE AND THE ALLEGED STRICTNESS OF THE SABINIANS - Kacprzak, Agnieszka (Zeszyty Prawnicze, 2018)
This paper concerns the famous controversy between the Sabinians and the Proculians on the consequences for the mandatary if he exceeded the limit of his mandate. According to the Sabinians, if a mandatary commissioned to buy a given good paid more than the price specifed by the mandator, he could not claim the restitution of any costs, not even to the limit specifed by the mandator. The Proculians’ opinion on the issue was more favourable to the mandatary, they permitted him to claim restitution of the costs up to the limit specifed in the mandate, provided he was prepared to hand the purchased item over to the mandator for the specifed price, viz. less than what he actually paid. In the literature on the subject the Proculians’ opinion is usually treated as self-evident. Most scholars tend to be surprised by the alleged strictness of the Sabinians. This paper argues that the Sabinian position is fully understandable both from the dogmatic and practical point of view, and that contrary to appearances the Proculian opinion leads to more troublesome consequences. One was the unequal status of the parties to the contract. The mandatary was free to buy the item and keep it for himself if it turned out to be more expensive than the mandator was willing to pay (G.3,161). Yet from the Proculian point of view, he could also decide to hand the item over to the mandatary for the price specifed in the mandate. Hence, it depended solely on the mandatary’s decision if the mandate was to be completed or not. In this article I suggest that one of the main reasons underlying the Sabinian position was to avoid this inequality. It follows from D. 17,1,3,2 that they actually raised this objection against the Proculian view. Their solution also protected the mandator from possible abuses on the part of the mandatary, who could have purchased the item for himself, and only on having discovered defects in it decided to hand it over to the mandator, thus recovering at least part of the price.